Concurrent Newborn Hearing and Genetic Screening in a Multi-Ethnic Population in South China - Tang, Xiangrong; Liu, Lihua; Liang, Sulan; Liang, Meie; Liao, Tao; Luo, Shiqiang; Yan, Tizhen; Chen, Jianping (Frontiers in Pediatrics, 2021)
Hearing loss is a common sensory deficit in humans with intricate genomic landscape and mutational signature. Approximately 1 - 3 out of 1,000 newborns have hearing loss and up to 60% of these cases have a genetic etiology. In this study, we conducted the concurrent newborn hearing and genetic screening in 20 mutations in GJB2, GJB3, SLC26A4 and MT-RNR1 for 9,506 normal newborns (4,977 [52.4%] males) from 22 ethnic population in South China. A total of 1,079 (11.4%) newborns failed to pass the initial hearing screening, 160 (23.9%) infants failed to pass the re-screening, and 128 (1.4%) infants presented the diagnostic hearing loss. For the genetic screening, 220 (2.3%) newborns presented at least one of the screened mutations were more likely to fail the hearing screening and have diagnostic hearing loss than mutation negative newborns. In comparison of the differences of distribution of mutations, we did not identify any significant difference in the prevalence of screened mutations between Han group (n = 5,265) and Zhuang group (n = 3,464), despite of the lack of number of minority ethnic groups. Studies including larger number of minority ethnic populations are needed in the future.